Ascertainment of Asthma Prognosis Using Natural Language Processing from Electronic Medical Records - Sohn, Sunghwan (J Allergy Clin Immunol, 2018)
NLP algorithm successfully determined asthma prognosis (i.e., no remission, long-term remission, and intermittent remission) by taking into account asthma symptoms documented in EMR, and addressed the limitations of billing code- based asthma outcome assessment.